Prevent Stunting Campaign: Dissemination of Health Information through Instagram - Khatimah, Khusnul; Laksmi, Laksmi (Record and Library Journal, 2019)
Background of the study: Dissemination of health information that is not properly managed can result in a lack of public knowledge in maintaining their health and lead to serious health problems, such as stunting.Purpose: The purpose of this study was to explore the use of Instagram as a tool for disseminating information related to stunting intervention in Indonesia.Method: This study used content analysis method to identify and analyze 354 uploads with the hashtag #cegahstunting on Instagram from August 2017 until December 2018.Findings: Results showed that most campaign messages were directly related to health, which were dominated by content about preventive efforts aimed at general audience. Most uploaders were organizations, namely the government and non-profit institutions.Conclusion: It is concluded that the role of individuals can be enhanced as relevant and trusted sources in creating and disseminating stunting-related information in Indonesia through social media. Information makers need to pay attention to the characteristics of the target group and the media used in order to create effective messages